Psikologi Pendidikan Islam dalam Al-Qur'an - Nuryahya, Ikhsan; Sriyanta, Sriyanta; Rohimah, Siti (Lembaga Yasin AlSys, 2025)
This study aims to examine the concept of Islamic Educational Psychology based on the values and principles contained in the Qur’an, and to analyze strategies for its application in the learning process. The background of this research lies in the importance of a holistic educational approach that views humans as both spiritual and social beings. The method used is library research, involving the review of primary and secondary sources such as tafsir texts, academic books, journals, and educational documents. The findings show that Islamic Educational Psychology is founded on Qur’anic principles, including fitrah, tawhid, role modeling, the integration of knowledge, gradual learning, character development, as well as reflection and motivation. The Qur’an also contributes to students’ psychological well-being by reinforcing Islamic identity, fostering emotional intelligence, enhancing learning motivation, and shaping noble character. Implementation strategies include the integration of values into the curriculum, the creation of an Islamic learning environment, teacher role modeling, family and community involvement, and continuous learning evaluation. The study concludes that Qur’an-based education can produce students who excel not only academically, but also spiritually and emotionally.